2016
DOI: 10.3390/healthcare4020023
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled and Retrospective Study of 144 Chronic Low Back Pain Patients to Evaluate the Effectiveness of an Intensive Functional Restoration Program in France

Abstract: Study Design: A controlled and retrospective study of 144 chronic low back pain patients to evaluate the effectiveness of an intensive functional restoration program in France. Objective: Evaluating the efficiency of an intensive, dynamic and multidisciplinary functional restoration program in patients with chronic low back pain (LBP), during 6 and 12 months follow up. Summary of background data: Chronic low back pain disease has a multifactor nature, involving physical, psychological professional and social f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Four different instruments were used to assess HRQoL (DPQ 55 ; Life Satisfaction Questionnaire 11; LiSat-11 60 ; SF-36 34 ; generic 15-dimensional self-administered 15D instrument 61 ), which probably contributed to the conflicting results. Three studies found no long-term increase in the HRQoL after MBR: Caby et al 43 found a short-term reduction in one HRQoL variable 43 and neither Rantonen et al 50 nor Merrick et al 48 detected any change in HRQoL (Table 4). The other 4 studies reported moderate to large increases in HRQoL that persisted for at least 12 months (ES 0.5 to 0.8; P < .05 to P < .001).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Four different instruments were used to assess HRQoL (DPQ 55 ; Life Satisfaction Questionnaire 11; LiSat-11 60 ; SF-36 34 ; generic 15-dimensional self-administered 15D instrument 61 ), which probably contributed to the conflicting results. Three studies found no long-term increase in the HRQoL after MBR: Caby et al 43 found a short-term reduction in one HRQoL variable 43 and neither Rantonen et al 50 nor Merrick et al 48 detected any change in HRQoL (Table 4). The other 4 studies reported moderate to large increases in HRQoL that persisted for at least 12 months (ES 0.5 to 0.8; P < .05 to P < .001).…”
Section: Resultsmentioning
confidence: 98%
“…Seventy of the remaining 83 articles did not meet the inclusion criteria, leaving a sample of 13 primary studies for review (Figure 1). 4054 Twelve studies examined the efficacy of MBR, 3 investigated cost-effectiveness, and 1 examined clinical utility. Three of the 13 studies examined 2 or more of these variables.…”
Section: Resultsmentioning
confidence: 99%
“…The authors measured the intensity of pain, mobility, the quality of life and the return to work. The obtained results were very good and the programme produced beneficial short-term and long-term effects [24]. Therefore, it is justified to apply such extensive physiotherapy in order to help patients to quickly resume their social activity.…”
Section: Discussionmentioning
confidence: 90%
“…Caby et al conducted research during which the effectiveness of intensive, dynamic, multidisciplinary and functional program in patients with back pain was evaluated [24]. The program included physiotherapy and occupational therapy treatments as well as psychological consultancy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other countries state that about 57% of patients in Europe and even 70% of patients in the US are able to restart regular full-time work and show significant improvements of psychosocial, physiological parameters after inpatient rehabilitation [40][41][42][43]. An interdisciplinary treatment of medical, physical activity based and psychological therapy ensures a high return to professional life [44,45].…”
Section: Efficacy and Sustainability Of Orthopedic Rehabilitationmentioning
confidence: 99%